Composite optical film and manufacturing method thereof

By adopting a three-layer composite optical film, including the first prism layer, the second prism layer and the diffusion layer, the problems of many materials, complex cutting and assembly and large thickness in traditional backlight module design are solved, and high optical gain, thinner design and production efficiency are improved.

CN119861436APending Publication Date: 2025-04-22苏州弘德光电材料科技有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510222605.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional backlight module designs have problems such as many materials, complex cutting and assembly, large thickness, and it is difficult to meet the thinning needs of modern electronic equipment.

Method used

A composite optical film with a three-layer structure, including a first prism layer, a second prism layer and a diffusion layer, uses precision bonding technology to achieve tight fit of each layer of materials, simplify the cutting and assembly process, and optimize the optical structure to improve optical gain.

Benefits of technology

It realizes high optical gain, thinner design, improves production efficiency and yield, reduces manufacturing costs, avoids material adsorption and wear problems, and enhances the stability and warping resistance of the overall structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861436A_ABST
    Figure CN119861436A_ABST
Patent Text Reader

Abstract

The invention relates to a composite optical film, which designs an integrated three-layer structure by integrating multiple layers of functional materials, and comprises a first prism layer, a second prism layer and a diffusion layer. According to the structure, the cutting and assembling processes are simplified, the production efficiency is improved, and high optical gain, high stiffness and excellent warping resistance are achieved through precise optical structure design. The second prism layer serves as a core layer and comprises a plurality of first prism structures and second prism structures which are arranged in parallel, the bottom width difference design is adopted, the diffusion layer adopts unique trapezoidal steps as a front diffusion structure, and the height, the distance and the sand blasting haze of the steps are controlled through the machining technology and the surface treatment technology. According to the invention, high-efficiency and uniform scattering of light is realized, the brightness and contrast of a display picture are improved, uneven brightness and glare phenomena are avoided, high-efficiency management and optimized output of light are realized, the brightness and contrast of the display picture are improved, and more comfortable and fine visual experience is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite optical film and a method for manufacturing the same. Background Art

[0002] LCD liquid crystal display technology occupies an important position in display devices due to its high definition and stable display performance. However, LCD liquid crystal display itself does not emit light and needs to rely on the backlight module to provide light source to realize image display. The core of the design of the backlight module is to efficiently convert the point light source into a uniform surface light source through a series of optical material components. In the traditional backlight module design, the prism plays a vital role. It uses a micro-prism structure to converge light to improve the front brightness and uniformity. At present, the backlight module generally uses two prisms with a high-haze lower diffusion film and a low-haze upper diffusion film to achieve the overall backlight concealment and brightening effect.

[0003] However, this traditional design has several problems. First, four sheets of optical film materials need to be cut and assembled four times, which not only increases the manufacturing cost but also reduces the assembly efficiency. In addition, the superposition of multiple layers of materials makes the overall backlight module thicker, which is difficult to meet the development trend of thinning modern electronic devices. Although some common solutions try to simplify the structure by combining a single sheet of material with multiple functions such as a brightness enhancement film, a light guide plate, and a diffuser, these solutions often fail to achieve ideal results in terms of brightness and uniformity.

[0004] In recent years, with the continuous advancement of display technology, the design of backlight modules has been continuously optimized. Despite some progress, composite optical films and their production methods still face some challenges. First of all, how to further simplify the optical film structure and reduce the number of material layers while ensuring brightness and uniformity is a problem that needs to be solved urgently. Secondly, how to optimize the bonding process between optical films to ensure that there are no bubbles or misalignments between the layers is also the key to improving the quality of backlight modules. In addition, with the continuous development of self-luminous display technologies such as OLED, the backlight module industry is also facing tremendous market competition pressure. How to reduce costs and improve production efficiency while ensuring performance will be an important research direction for composite optical films and their production methods in the future. Summary of the invention

[0005] The purpose of the present application is to provide a composite optical film, which improves the process yield, cutting and assembly efficiency, and ensures sufficient brightness visual performance, while reducing the overall thickness. Compared with the traditional solution of using multiple materials together, the three-layer bonding product achieves close bonding between the layers of materials through design and manufacturing process, avoiding the problems of adsorption and abrasion of each material, thereby directly improving the process yield. In addition, the integration of the three-layer structure also greatly simplifies the cutting and assembly process and improves production efficiency. The composite optical film of the present application includes a first prism layer, a second prism layer and a diffusion layer; The second prism layer is disposed on the diffusion layer via a second adhesive layer, and the first prism layer is disposed on the second prism layer via a first adhesive layer; The second prism layer includes a plurality of first prism structures and a plurality of second prism structures arranged in parallel, the cross-sectional shapes of the first prism structures and the second prism structures are quasi-isosceles triangles and have the same vertex angles, and the bottom width of the first prism structure is greater than the bottom width of the second prism structure; The diffusion layer comprises a front diffusion structure, the front diffusion structure is a trapezoidal step, and the second adhesive layer is located between the top surface of the trapezoidal step and the bottom surface of the second prism layer.

[0006] In one embodiment, the first prism structure and the second prism structure are arranged at intervals, the interval between the first prism structure and the second prism structure is in the range of 15 μm-70 μm, and the bottom width of the first prism structure is 1.2 times to 1.5 times the bottom width of the second prism structure.

[0007] In one of the embodiments, the prisms in the first prism layer randomly shake up and down, and the shaking height difference is in the range of 2-3 μm.

[0008] In one embodiment, the first prism layer includes a plurality of third prism structures and a plurality of fourth prism structures, the number of the fourth prism structures is more than twice the number of the third prism structures, and the bottom width of the third prism structure is greater than the bottom width of the fourth prism structure.

[0009] In one of the embodiments, the diffuse haze of the step portion in the trapezoidal step is in the range of 75%-95%.

[0010] In one embodiment, the haze of the first adhesive layer and the second adhesive layer is in the range of 20%-40%.

[0011] In addition, the present application also provides a method for manufacturing a composite optical film, comprising: Making a first prism layer, specifically comprising providing a first substrate, and making prisms on the first substrate by transfer-curing a photocurable adhesive; Manufacturing the second prism layer specifically includes providing a second substrate, and manufacturing a plurality of first prism structures and a plurality of second prism structures arranged in parallel on the second substrate by transfer-curing a photocurable adhesive; Manufacturing the diffusion layer specifically includes providing a third substrate, and using a trapezoidal mold to emboss to form a front diffusion structure on the third substrate; A first adhesive layer is formed on the back side of the first substrate layer of the first prism layer, and a second adhesive layer is formed on the back side of the second substrate layer of the second prism layer, so that the first prism layer, the second prism layer and the diffusion layer form an integrated three-layer structure.

[0012] In one embodiment, in the steps of forming the first adhesive layer and forming the second adhesive layer, a sandblasting mist roller mold is used.

[0013] In one of the embodiments, the step of forming the front diffusion structure further includes sandblasting the surface of the trapezoidal mold.

[0014] In one of the embodiments, a haze layer is formed on the back side of the diffusion layer.

[0015] Compared with the prior art, this application has the following beneficial effects: The composite optical film of the present application achieves high optical gain through the integration of a three-layer structure. The design of the first prism layer and the second prism layer, especially the multiple first prism structures and multiple second prism structures arranged in parallel in the second prism layer, as well as their isosceles triangle-like cross-sectional shapes and specific base-width ratios, effectively improve the ability to converge and guide light, thereby enhancing the overall optical gain. At the same time, the front diffusion structure in the diffusion layer, such as the trapezoidal step design, further optimizes the diffusion effect of light, ensuring a dual improvement in brightness and uniformity.

[0016] By using the second adhesive layer and the first adhesive layer, a stable connection between the layers is ensured, and the rigidity and stability of the overall structure are enhanced, thereby effectively resisting warping and deformation. Furthermore, the composite optical film of the present application avoids the problems of adsorption and abrasion of each material, thereby directly improving the process yield. The close fit between the layers of material, as well as the specific prism structure and diffusion structure design, effectively reduce the friction and adsorption between the materials, and reduce the risk of damage that may occur during the manufacturing and assembly process. The integration of the three-layer structure also greatly simplifies the cutting and assembly process and improves production efficiency. Compared with the traditional solution of using multiple materials, the composite optical film of the present application reduces the number of cutting and assembly times, reduces manufacturing costs, and at the same time improves assembly efficiency and overall production flexibility.

[0017] In a specific embodiment, designs such as the spaced arrangement of the first prism structure and the second prism structure, the random up and down shaking of the prism, and the combination of a specific number of third prism structures and fourth prism structures further enhance the optical performance and improve the light utilization and uniformity. At the same time, detailed designs such as the specific diffusion haze of the step part in the trapezoidal step and the haze control of the adhesive layer also ensure the stability and consistency of the overall optical performance. Finally, the method for making a composite optical film provided in the present application further improves the quality and consistency of the product by controlling the production and bonding process of each layer of material, such as using a sandblasting haze roller mold to form an adhesive layer and sandblasting the surface of the trapezoidal mold. In addition, a haze layer can be optionally formed on the back of the diffusion layer to further enhance the optical performance and adaptability of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a schematic diagram of the main structure of the composite optical film in the embodiment of the present application; Figure 2 is a schematic diagram of the cross-sectional structure of the composite optical film in the embodiment of the present application; Figure 3 is a schematic diagram of the main structure of the second prism in the composite optical film in the embodiment of the present application; Figure 4 It is a schematic diagram of the main structure of the diffusion layer in the composite optical film in the embodiment of the present application.

[0019] Explanation of reference numerals: 100, first prism layer; 200, second prism layer; 210, first prism structure; 220, second prism structure; 300, diffusion layer; 310, front diffusion structure. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0021] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0022] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0023] Traditional backlight module designs usually use multiple optical film materials in combination to achieve light convergence, diffusion and brightening. However, this design not only increases manufacturing costs and assembly complexity, but also fails to meet the requirements of modern electronic devices for thinness and high efficiency. In order to meet these challenges, this application proposes a new composite optical film and a method for making it. The composite optical film of this application integrates multiple layers of functional materials to form an integrated three-layer structure, including a first prism layer, a second prism layer and a diffusion layer. This design not only simplifies the cutting and assembly process and improves production efficiency, but also achieves high optical gain, high stiffness and anti-warping performance through precise optical structure design. At the same time, the close fit between the layers of material effectively avoids adsorption and abrasion problems between materials, thereby improving the process yield. Please refer to Figures 1 to 4 The composite optical film in a preferred embodiment of the present application includes a first prism layer 100, a second prism layer 200 and a diffusion layer 300, wherein the second prism layer 200 is arranged on the diffusion layer 300 through a second adhesive layer, the first prism layer 100 is arranged on the second prism layer 200 through a first adhesive layer, the second prism layer 200 includes a plurality of first prism structures 210 and a plurality of second prism structures 220 arranged in parallel, the cross-sectional shapes of the first prism structures 210 and the second prism structures 220 are isosceles triangle-like and have the same vertex angle, the bottom width of the first prism structure 210 is greater than the bottom width of the second prism structure 220, the diffusion layer 300 includes a front diffusion structure 310, the front diffusion structure 310 is a trapezoidal step, and the second adhesive layer is located between the top surface of the trapezoidal step and the bottom surface of the second prism layer 200.

[0024] The composite optical film of the present application realizes efficient management and optimized output of light through a three-layer structure design. The composite optical film specifically comprises a first prism layer 100, a second prism layer 200 and a diffusion layer 300, and each layer is closely connected to form a whole through bonding technology. The first prism layer 100 is closely attached to the second prism layer 200 through the first bonding layer, and the incident light is accurately guided through a specific prism structure to achieve preliminary convergence and directional transmission of the light. The second prism layer 200 is the core layer of the composite optical film. The second prism layer 200 is arranged on the diffusion layer 300 through the second bonding layer. The layer includes a plurality of first prism structures 210 and a plurality of second prism structures 220 arranged in parallel, and the cross-sectional shapes are all isosceles triangles, and the vertex angles are consistent. The bottom width of the first prism structure 210 is designed to be larger than the bottom width of the second prism structure 220, which optimizes the convergence effect of light and enhances the transmission efficiency of light between the prism structures. The diffusion layer 300 in the present application adopts a unique trapezoidal step as the front diffusion structure 310, which not only increases the diffusion area of ​​the light, but also realizes the uniform distribution of the light through the trapezoidal inclined structure. The second adhesive layer is located between the top surface of the trapezoidal step and the bottom surface of the second prism layer 200, ensuring the seamless transmission of light between the two layers and avoiding light loss and image distortion.

[0025] Through the prism structure and the diffusion layer 300, the composite optical film can achieve precise control and efficient output of the incident light, improve the brightness and contrast of the display screen, and the application of the trapezoidal step diffusion structure makes the light more uniform during the output process, avoiding uneven brightness and glare, and providing users with a more comfortable visual experience. The layers are closely connected through precise bonding technology to form a stable and reliable overall structure, which effectively resists interference and damage from the external environment and prolongs the service life of the composite optical film.

[0026] Specifically, the first prism structure 210 and the second prism structure 220 are arranged at intervals, the spacing between the first prism structure 210 and the second prism structure 220 is in the range of 15μm-70μm, and the bottom width of the first prism structure 210 is 1.2 times-1.5 times the bottom width of the second prism structure 220. The above design not only optimizes the transmission path of the light, but also enhances the interaction of the light between the prism structures, thereby improving the overall optical performance. More importantly, the selection of the spacing range between the first prism structure 210 and the second prism structure 220 ensures that the light can maintain sufficient interaction between the prism structures and avoid excessive scattering and loss, thereby achieving efficient convergence and directional transmission of the light. The proportional relationship between the bottom width of the first prism structure 210 and the bottom width of the second prism structure 220 further optimizes the convergence effect of the light, so that the light can form a smoother and continuous light distribution when passing through the prism structures with different bottom widths, which not only improves the brightness and uniformity of the displayed image, but also enhances the three-dimensional sense and layering of the image, providing a more delicate and realistic visual experience. The linear structure spacing between the first prism structure 210 and the second prism structure 220 is 15-70 μm, the prism bottom width is 1 wide and 1 narrow, the bottom width of the large prism is 1.2-1.5 times the bottom width of the small prism, the application preferably uses 57 μm for the large prism and 45 μm for the small prism, and the magnification relationship is preferably 1.26.

[0027] Specifically, the prisms in the first prism layer 100 randomly shake up and down, and the height difference of the shake is in the range of 2~3μm. By introducing the random up and down shake design of the prism in the first prism layer 100, a more complex and changeable transmission path is provided for the light, which not only enhances the interaction between the light in the prism structure, but also enables the light to form a more delicate and uniform light distribution when passing through the prism layer. The jitter height difference is controlled within the above range. This adjustment ensures that the scattering and refraction of light between the prisms can be maintained in the optimal state, which not only avoids excessive light loss, but also improves the utilization rate and convergence effect of light. This design is effective in improving the quality of the display image, making the light distribution on the display panel more even, reducing the excessive concentration or loss of light in specific areas, thereby effectively eliminating the bright and dark spots in the picture.

[0028] Specifically, the first prism layer 100 includes a plurality of third prism structures and a plurality of fourth prism structures, the number of the fourth prism structures is more than twice the number of the third prism structures, and the bottom width of the third prism structure is greater than the bottom width of the fourth prism structure. In terms of the arrangement of the bottom width of the prisms, not only can the equal spacing be selected, but the spacing is preferably 24μm (within the range of 18 to 50μm). This fine adjustment ensures that the transmission of light between the prism structures can remain efficient and stable. In addition, another arrangement method can be adopted, namely the "1 wide n narrow" prism combination, in which the bottom width of the large prism (third prism structure) is 1.5 to 2 times the bottom width of the small prism (fourth prism structure), which not only further optimizes the transmission path of light, but also improves the brightness and uniformity of the display screen. By precisely controlling the number, bottom width and arrangement of prisms, the present application makes the distribution of light on the display panel more uniform, which helps to enhance the three-dimensional sense and layering of the picture, making the display picture more delicate, vivid and realistic, and bringing a more immersive visual experience to users. The vertex angles of the first prism structure 210 , the second prism structure 220 , the third prism structure and the fourth prism structure are in the range of 88° to 92°, preferably in the range of 90±1°.

[0029] The diffusion layer 300 of the composite optical film structure introduces a trapezoidal step design with a specific diffusion haze range and geometric parameters to further achieve efficient and uniform scattering of light and improve display quality, thereby bringing multiple significant technical effects and visual experience optimization. Specifically, the diffusion haze of the step part of the trapezoidal step design in this application is adjusted to within the range of 75%-95%, ensuring that the light can be fully and evenly scattered when passing through the trapezoidal step, effectively breaking the straight-line propagation path of the light, so that the light can be more widely and evenly distributed on the display panel, which not only improves the brightness uniformity and viewing angle width of the display screen, but also further assists in eliminating dark corners and uneven brightness in the screen.

[0030] In terms of the geometric parameters of the trapezoidal steps, the top width of the steps is set to 5~10μm. This size range ensures that light can be effectively scattered at the top of the steps, while avoiding excessive scattering and blurred images due to excessive size. The height of the trapezoid is controlled within the range of 20~50μm. This height design not only ensures that light can be fully scattered inside the steps, but also avoids light loss and reduced image brightness due to excessive height. In addition, the bottom angle is set to 38°, and the trapezoidal spacing is set to 60~90μm. The trapezoidal step design improves the visual effect of the display screen, and also shows good processing adaptability and stability, achieving efficient and uniform scattering of light, and improving display quality.

[0031] In the composite optical film structure of the present application, efficient and stable bonding between the prism layer and the diffusion layer 300 is achieved by optimizing the properties of the first adhesive layer and the second adhesive layer, while retaining the key haze properties. Specifically, the first adhesive layer and the second adhesive layer are designed to have a haze range of 20%-40%. This haze property not only effectively balances the scattering and transmission of light, so that the light can form a softer and more uniform light distribution when passing through the adhesive layer, but also enhances the softness and visual comfort of the display image. The selection of this haze range also ensures that the adhesive layer can maintain good light transmittance during the bonding process, avoiding light loss and blurred images due to excessive haze.

[0032] In terms of adhesive performance, the first adhesive layer and the second adhesive layer are not less than 50gf / 25mm. The adhesive peeling force within this range ensures that the prism layer and the diffusion layer 300 can be tightly and firmly bonded together, effectively preventing interlayer separation or peeling caused by external forces, which not only improves the overall structural stability and durability of the composite optical film, but also ensures that the display screen can maintain excellent display effects and image quality stability during long-term use. By introducing an adhesive layer with specific haze characteristics, not only is efficient bonding between the prism layer and the diffusion layer 300 achieved, but the key haze layer is also retained, thereby improving the overall visual effect of the display screen, making the light distribution on the display panel more uniform and soft, and effectively eliminating glare and glare in the screen.

[0033] In addition, the present application also provides a method for manufacturing a composite optical film, comprising the following steps: The first prism layer 100 is manufactured, specifically comprising providing a first substrate, and manufacturing prisms on the first substrate by transfer-curing a photocurable adhesive; The second prism layer 200 is manufactured, specifically comprising providing a second substrate, and transferring and curing a photocurable adhesive on the second substrate to manufacture a plurality of first prism structures 210 and a plurality of second prism structures 220 arranged in parallel; Manufacturing the diffusion layer 300 specifically includes providing a third substrate, and using a trapezoidal mold to emboss and form a front diffusion structure 310 on the third substrate; A first adhesive layer is formed on the back side of the first substrate layer of the first prism layer 100 , and a second adhesive layer is formed on the back side of the second substrate layer of the second prism layer 200 , so that the first prism layer 100 , the second prism layer 200 and the diffusion layer 300 are formed into an integrated three-layer structure.

[0034] In the above-mentioned composite optical film structure, high-performance materials are used in the selection of the substrate layer to ensure excellent optical performance and stability. Specifically, the substrate layer mainly uses a PET (polyethylene terephthalate) substrate with a thickness of 25~250μm. This material not only has good mechanical strength and weather resistance, but also performs well in optical properties. In addition, in order to meet the needs of different application scenarios, the present invention may also use other high-transmittance optical grade materials such as PC (polycarbonate) or PMMA (polymethyl methacrylate) as alternative options for the substrate layer. However, in a preferred embodiment of the present application, a PET material with a thickness of 25μm is specifically selected as the substrate layer, which exhibits a transmittance of more than 90% and an extremely low haze of less than 1%.

[0035] The prism structure of the composite optical film structure uses metal roller mold processing technology to ensure that the designed prism microstructure can be accurately and efficiently copied to the optical film. In the mold making process, ultraviolet light curing acrylic resin (UV glue) can be used as the transfer material. Through the curing and molding process of UV glue, the prism microstructure can be accurately replicated and formed with high precision. In order to ensure that the upper prism structure can withstand certain physical impacts in practical applications, especially tests such as falling ball impact, strict requirements are imposed on the performance of UV glue. UV glue not only needs to have excellent curing performance and molding accuracy, but also needs to have excellent anti-falling ball impact effect to ensure that the prism structure can maintain structural integrity and stability during long-term use. In addition, the refractive index of UV glue is also selected. As an important parameter of optical materials, the refractive index has an important influence on the propagation and refraction of light. The refractive index of UV glue is preferably 1.64~1.67. This refractive index range not only matches the refractive index of commonly used optical materials such as PET substrates, but also ensures that light can be effectively refracted and focused when passing through the prism structure, thereby improving the brightness and clarity of the display screen. By adopting precise metal roller mold processing technology and high-performance UV adhesive materials, accurate replication and high-precision molding of the prism structure in the first prism layer 100 are achieved, while ensuring the stability and reliability of the prism structure in practical applications.

[0036] The substrate of the first prism layer 100 uses high-performance materials to ensure excellent optical performance and structural stability. Specifically, the substrate of the first prism layer 100 mainly uses PET (polyethylene terephthalate) material with a thickness of 25~250μm, which not only has good mechanical strength and weather resistance, but also has excellent optical performance, and is particularly suitable for the production of high-precision prism structures. In order to meet the needs of different application scenarios, other high-transmittance optical grade materials such as PC (polycarbonate) or PMMA (polymethyl methacrylate) can also be used as alternative options for the substrate of the first prism layer 100. However, in a preferred embodiment of the present application, a PET material with a thickness of 25μm is specially selected as the substrate of the first prism layer 100. The material exhibits a transmittance of more than 90%, ensuring that the light can maintain high clarity when passing through the prism structure; at the same time, its haze is controlled within 1%, effectively avoiding the scattering and loss of light inside the substrate, thereby further improving the clarity and brightness of the display. By adopting the above-mentioned preferred PET substrate, not only the high-precision production and excellent optical performance of the first prism layer 100 are achieved, but also the stability and reliability of the composite optical film structure during long-term use are ensured.

[0037] The adhesive layer uses a special UV-curable acrylic resin material, and combined with precise sandblasting haze roller mold technology, a bonding layer with specific haze characteristics is formed on the back of the first prism layer 100. To ensure the close fit between the adhesive layer and the first prism layer 100, the light distribution and visual effects of the display screen are further optimized by introducing the haze structure. Specifically, the special UV-curable acrylic resin material has the characteristics of being removable and demoldable and maintaining viscosity after pre-curing. This characteristic enables the material to be precisely formed on the sandblasting haze roller mold and maintain shape stability and viscosity during the pre-curing stage. The sandblasting structure uses 10~90μm diamond grains to pre-produce a surface with a specific roughness on the metal roller mold, which interacts with the UV glue during the embossing process, so that the UV glue can form a structural layer with haze characteristics after curing and firmly adhere to the substrate. Furthermore, by precisely controlling the sandblasting structure and the curing process of the UV glue, the haze structure can be precisely controlled within the range of 20% to 40%, with the preferred haze value being 25%, thereby effectively scattering light, reducing glare and reflection on the screen, and improving the softness and layering of the screen, providing users with a more comfortable visual experience. The refractive index of the UV glue has also been carefully selected, and the refractive index is preferably 1.45 to 1.55, with 1.47 being the most preferred, which matches the refractive index of commonly used optical materials such as PET substrates, and can also ensure that light can be effectively refracted and focused when passing through the adhesive layer, thereby further improving the brightness and clarity of the displayed screen.

[0038] The prism microstructure in the second prism layer 200 is made by high-precision metal roller mold processing technology to ensure that the designed prism structure can be accurately and efficiently copied to the optical film. In the molding process of the prism structure, UV-curable acrylic resin is used as the transfer material. The refractive index of the UV glue is preferably 1.64~1.67 in this application to ensure that the light can be effectively refracted and focused when passing through the prism structure. The substrate of the second prism layer 200 uses high-performance materials to ensure excellent optical performance and structural stability. Specifically, the substrate of the second prism layer 200 mainly uses PET (polyethylene terephthalate) material with a thickness of 25~250μm. This material not only has good mechanical strength and weather resistance, but also has excellent optical performance, and is particularly suitable for the production of high-precision prism structures. In order to meet the needs of different application scenarios, other high-transmittance optical grade materials such as PC (polycarbonate) or PMMA (polymethyl methacrylate) can also be used as an alternative option for the substrate of the second prism layer 200. However, in a preferred embodiment of the present application, a PET material with a thickness of 25 μm is specially selected as the substrate of the second prism layer 200, which exhibits a light transmittance of more than 90%, ensuring that the light can maintain high clarity when passing through the prism structure; at the same time, the haze is controlled within 1%, effectively avoiding the scattering and loss of light inside the substrate.

[0039] The diffusion layer 300 adopts mechanical processing technology and surface treatment technology, and uses trapezoidal tool turning technology to accurately turn the copper roller mold. In this process, the turning depth is controlled within the range of 20-50μm to ensure that the height of the step structure is moderate, which can effectively diffuse the light without excessively affecting the transmission efficiency of the light. At the same time, the spacing between the steps is set to 60-90μm to optimize the scattering angle and distribution of the light. In a preferred embodiment of the present application, a height of 25μm and a spacing of 90μm are specially selected as parameters of the step diffusion structure. This combination can ensure effective diffusion of light while maintaining high light transmittance and clarity. The surface of the mold roller that has been turned is sandblasted. The sandblasting uses corundum as an abrasive, and the diameter of the corundum is controlled within the range of 10-90μm to ensure the uniformity and stability of the sandblasting effect. By adjusting the parameters of the sandblasting process, such as sandblasting time and pressure, the roughness and haze of the mold roller surface can be controlled. In the present application, the sandblasting haze is preferably 75%, which can ensure effective scattering of light while avoiding image blur and brightness loss caused by excessive scattering.

[0040] Regarding the substrate of the diffusion layer 300, high-performance materials are also used to ensure excellent optical performance and structural stability. Specifically, the substrate of the diffusion layer 300 mainly uses PET (polyethylene terephthalate) material with a thickness of 25-250μm. PET material not only has good mechanical strength and weather resistance, but also has excellent optical performance, and is particularly suitable for the production of high-precision optical films. In order to meet the needs of different application scenarios, other high-transmittance optical grade materials such as PC (polycarbonate) or PMMA (polymethyl methacrylate) can also be used as alternative options for the substrate of the diffusion layer 300. However, in a preferred embodiment of the present application, a PET material with a thickness of 50μm is particularly selected as the substrate of the diffusion layer 300. The material exhibits a transmittance of more than 90%, ensuring that the light can maintain high clarity when passing through the diffusion layer 300; at the same time, its haze is controlled within 1%, which can further effectively avoid the scattering and loss of light inside the substrate.

[0041] A haze layer is disposed on the back of the diffusion layer 300, and a haze layer with a rough surface is designed on the back of the diffusion layer 300, and its haze value is controlled within the range of 2% to 10%. In order to obtain a better UV transfer effect, it is preferred to use a sandblasting roller with a haze value of 10% for processing, so as to achieve an efficient production process of one-time curing and molding. In addition, in the steps of forming the first adhesive layer and forming the second adhesive layer, a sandblasting haze roller mold is used.

[0042] In the detailed steps of forming the front diffusion structure 310, a pretreatment process is used to perform fine sandblasting on the surface of the trapezoidal mold. The sandblasting uses hard abrasives such as corundum to spray onto the mold surface at a certain speed and pressure, thereby forming a uniform and fine rough structure on the mold surface. This rough structure can effectively interact with the UV glue material in the subsequent UV transfer process, so that the UV glue can form a fine structure matching the mold surface structure after curing.

[0043] A haze layer with a specific haze value is formed on the back of the diffusion layer 300. The haze layer is formed by making a rough surface on the back of the diffusion layer 300 and controlling the haze value of the surface within a range of 2% to 10%. The rough surface of the haze layer formed on the back of the diffusion layer 300 can effectively scatter light, so that the light can be more evenly distributed when passing through the diffusion layer 300. Although the presence of the haze layer will increase the scattering of light, by accurately controlling the haze value within a range of 2% to 10%, it can be ensured that the light can still maintain a high transmittance while being scattered. This balance allows the display to maintain high clarity while showing softer and more natural colors.

[0044] The following will further introduce the comparison between the specific implementation method of the present application and the comparative example to further illustrate the technical solution of the present application in detail. The comparative example is formed by cutting and assembling four traditional independent materials.

[0045] The experimental test results of the above embodiments show that the technical solution proposed in this application has advantages in optical performance and application benefits. This solution not only has an optical gain effect equivalent to or even better than that of a single optical film stack, ensuring the excellence of the backlight module in optical performance, but also effectively avoids the adsorption risk that may occur during the use of the backlight module through a unique design, and improves the stability and reliability of the backlight module. The higher shielding performance demonstrated by the technical solution of this application has an inhibitory effect on process defects in practical applications. In the manufacturing process, problems such as light leakage and stray light interference caused by various factors will be effectively controlled, thereby improving the yield rate and overall quality of the product.

[0046] In addition, this application also demonstrates excellent efficiency in the cutting and assembly process. By optimizing the design and material selection, the cutting process is made more accurate and faster, and the assembly process is simplified, thereby greatly improving production efficiency. In addition, a breakthrough has been achieved in thickness control, providing a thinner thickness design, which is in line with the current market trend of thinning and lightweight electronic products, allowing the backlight module to be better integrated into various thin and light electronic products while maintaining high performance.

[0047] In summary, the technical solution of the present application has demonstrated advantages in optical gain, adsorption risk control, shielding performance improvement, cutting and assembly efficiency, and thickness control.

[0048] The above is only a specific implementation of the present application, and any other improvements made based on the concept of the present application are deemed to be within the protection scope of the present application.

Claims

1. A composite optical film, characterized in that: It comprises a first prism layer (100), a second prism layer (200) and a diffusion layer (300); The second prism layer (200) is arranged on the diffusion layer (300) via a second adhesive layer, and the first prism layer (100) is arranged on the second prism layer (200) via a first adhesive layer; The second prism layer (200) comprises a plurality of first prism structures (210) and a plurality of second prism structures (220) arranged in parallel, the cross-sectional shapes of the first prism structures (210) and the second prism structures (220) are quasi-isosceles triangles and have the same vertex angle, and the base width of the first prism structure (210) is greater than the base width of the second prism structure (220); The diffusion layer (300) comprises a front diffusion structure (310), the front diffusion structure (310) is a trapezoidal step, and the second adhesive layer is located between the top surface of the trapezoidal step and the bottom surface of the second prism layer (200); The first prism layer (100), the second prism layer (200) and the diffusion layer (300) are an integrated three-layer structure.

2. The composite optical film according to claim 1, characterized in that: The first prism structure (210) and the second prism structure (220) are arranged at intervals, the interval between the first prism structure (210) and the second prism structure (220) is in the range of 15 μm-70 μm, and the bottom width of the first prism structure (210) is 1.2 times-1.5 times the bottom width of the second prism structure (220).

3. The composite optical film according to claim 1, characterized in that: The prisms in the first prism layer (100) randomly shake up and down, and the shaking height difference is in the range of 2-3 μm.

4. The composite optical film according to claim 3, characterized in that: The first prism layer (100) comprises a plurality of third prism structures and a plurality of fourth prism structures, the number of the fourth prism structures is more than twice the number of the third prism structures, and the bottom width of the third prism structure is greater than the bottom width of the fourth prism structure.

5. The composite optical film according to claim 1, characterized in that: The diffusion haze of the step portion in the trapezoidal step is in the range of 75%-95%.

6. The composite optical film according to claim 1, characterized in that: The haze of the first adhesive layer and the second adhesive layer is in the range of 20%-40%.

7. A method for producing a composite optical film, characterized in that: include: Manufacturing a first prism layer (100), specifically comprising providing a first substrate, and manufacturing prisms on the first substrate by transfer-curing a photocurable adhesive; Manufacturing a second prism layer (200), specifically comprising providing a second substrate, and manufacturing a plurality of first prism structures (210) and a plurality of second prism structures (220) arranged in parallel on the second substrate by transfer-printing and curing a photocurable adhesive; Manufacturing a diffusion layer (300), specifically comprising providing a third substrate, and using a trapezoidal mold to emboss the third substrate to form a front diffusion structure (310); A first adhesive layer is formed on the back side of the first substrate layer of the first prism layer (100), and a second adhesive layer is formed on the back side of the second substrate layer of the second prism layer (200), so that the first prism layer (100), the second prism layer (200) and the diffusion layer (300) are formed into an integrated three-layer structure.

8. The method for manufacturing a composite optical film according to claim 7, characterized in that: In the steps of forming the first adhesive layer and forming the second adhesive layer, a sandblasted mist roll mold is used.

9. The method for manufacturing a composite optical film according to claim 7, characterized in that: The step of forming the front diffusion structure (310) further includes sandblasting the surface of the trapezoidal mold.

10. The method for manufacturing a composite optical film according to claim 7, characterized in that: The method also includes forming a haze layer on the back side of the diffusion layer (300).

Citation Information

Cited By

  • Optical film capable of effectively improving moire patterns, composite brightness enhancement film and backlight module

    CN120522937A